What role for profits and luxury consumption in the ecological transition? - Federica Cappelli; Stefano Di Bucchianico (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
Given the empirical evidence showing the crucial role of income distribution and excessive consumption of richer households in determining greenhouse gas emissions, understanding their connection becomes especially important. Building on the distinction between subsistence and luxury emissions, we study where to intervene in reducing non-essential emissions. In doing so, we are able to connect the double role of luxury goods. Together with surplus production of other wage-goods, they are the reason why profits exist, but they are also the major constituent of wasteful luxury consumption and, hence, major drivers of consumer-generated greenhouse gas emissions. Among the three different scenarios ('greener consumption', 'reformist', and 'just transition') we depict, only the just transition is a viable option to respect both social and environmental boundaries.
Keywords: Q57; Q52; B24; 330; rate of profit; luxury goods; GHG emissions; just transition; climate change